Effects of myofascial release techniques on joint range of motion of athletes: A systematic review and meta-analysis of randomized controlled trials - Antohe, B. A.; Alshana, O.; Uysal, H. S.; Rata, M.; Iacob, G. S.; Panaet, E. A. (Sports, 2024)
Although myofascial release techniques (MRTs) are commonly used to improve athletes` range of motion (ROM), the effectiveness of MRTs may vary depending on the specific method performed. This systematic review and meta-analysis aimed to evaluate the effects of MRTs on the ROM performance of athletes. (2)